2020
DOI: 10.3390/coatings10020123
|View full text |Cite
|
Sign up to set email alerts
|

Post-Process Treatments on Supersonic Cold Sprayed Coatings: A Review

Abstract: Cold Gas Dynamic Spray or Supersonic Cold Spray, or simply ‘Cold Spray’, is an emerging technology for rapidly building thin films, thick coatings and large-scale additive manufacturing at relatively low temperatures. In a cold spray process, particles are accelerated to supersonic speeds by a propellant gas and impact a substrate, thus producing a strong bonding with the substrate and subsequently forming a deposit via layer-by-layer buildup. The scalability and low cost of this method make it promising for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 96 publications
(218 reference statements)
0
27
0
Order By: Relevance
“…The resistance on tensile testing and the hardness of Ag irregular powder CGS sprayed coatings were higher than the Ag spherical shape, even after heat treatment [17]. Some mechanisms collaborate to the adhesion of the particles to the substrate as listed by Sun et al [18]: the adiabatic shear instability (ASI), caused by the high velocity of the powder particle, breaks the natural oxide film on the surface of both the particle and the substrate and the progressive plastic flow of the materials enables metallic bonding at atomic scale through direct contact between the adjacent fresh metal surfaces; mechanical interlocking, interfacial mixing, local melting and diffusion [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The resistance on tensile testing and the hardness of Ag irregular powder CGS sprayed coatings were higher than the Ag spherical shape, even after heat treatment [17]. Some mechanisms collaborate to the adhesion of the particles to the substrate as listed by Sun et al [18]: the adiabatic shear instability (ASI), caused by the high velocity of the powder particle, breaks the natural oxide film on the surface of both the particle and the substrate and the progressive plastic flow of the materials enables metallic bonding at atomic scale through direct contact between the adjacent fresh metal surfaces; mechanical interlocking, interfacial mixing, local melting and diffusion [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 91%
“…The CGS hardness values should be compared to other thermally sprayed 316L coatings: 190 HV [48] for flame spraying, 270 HV [48] and 312 HV [49] for HVOF, 325 HV for arc spraying [50], and 262 HV for APS [49]. The CGS process characteristics of lower temperature and higher velocity of particles than other processes justify its higher coating hardness, since its higher particles' velocity promotes the increasing in hardness due to their plastic strain hardening [51], and the relative low temperature prevents the material recrystallization, thus enabling the ASI mechanism, as explained by Sun et al [18]. In addition, all the coatings show a hardness in the range to that reported for 316L bulk materials, 350 HV 0.3 , approximately.…”
Section: Characterization Of Coatingsmentioning
confidence: 99%
“…The functionalities of metal/oxide thin films depend on the physical properties of the constituents and on the microscopic interactions at the film/substrate interface. Several factors such as the morphology, composition, crystalline phase and porosity of the materials may be controlled by synthesis methods such as cold gas dynamic spray [1], jet printing [2], supersonic cluster beam deposition (SCBD) [3,4], sol-gel methods [5][6][7][8], magnetron sputtering [9][10][11][12] and dip-coating [13]. Post-deposition annealing treatments can further tweak the film behaviour, bringing the substrate properties into play.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that heat treatment or hot isostatic pressing could signi cantly improve the mechanical properties of cold spray deposits [15,[20][21][22][23][24]. In these processes, the high temperature enhance the material diffusion through the particle-particle interface and lead to formation of joint grains between neighbor particles.…”
Section: Introductionmentioning
confidence: 99%
“…At present, many articles devoted to the friction stir processing of cold spray despots are available in literature [20,[33][34][35][36][37][38][39][40][41][42]. The major part of these works deal mainly with FSP treatment of relatively soft materials like aluminum and copper alloys [33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%